Leukocyte‐borne α(1, 3)‐fucose is a negative regulator of β2‐integrin‐dependent recruitment in lung inflammation. Issue 2 (26th August 2016) - Buffone, Alexander; Nasirikenari, Mehrab; Manhardt, Charles T.; Lugade, Amit; Bogner, Paul N.; Sackstein, Robert; Thanavala, Yasmin; Neelamegham, Sriram; Lau, Joseph T. Y.
Abstract : Leukocyte recruitment in inflammation is a multistep, sequential cascade where the initial step is the selectin‐dependent tethering, followed by the formation of firmer integrin‐mediated adhesive forces leading to extravasation. The α(1, 3)‐fucose‐containing sialyl‐Lewis X (sLe X ) is the archetypical ligand on leukocyte surfaces mediating selectin interactions. Canonically, disruption of α(1, 3)‐fucose formation ablates selectin‐mediated adhesion, dramatically reducing trafficking. We report a paradoxical response to α(1, 3)‐fucose deficiency in which the loss exacerbated rather than attenuated leukocyte recruitment in a murine model of acute airway inflammation. The architecture of the capillary‐dominated vasculature in the lung minimized the importance of the selectin dependent step, and we observed that α(1, 3)‐fucose deficiency augmented CXCR2‐mediated Rap1‐GTP signaling to enhance the β2 ‐integrin‐ICAM‐1‐binding axis. The data disclose a previously unknown function for α(1, 3)‐fucose, in which this structure negatively regulates the integrin activation step in leukocyte recruitment.